Seasonal fluctuations and diversity of Ingoldian mycobiota in two water bodies receiving different effluents at Assiut Governorate (Upper Egypt) - Abdel-Raouf M. Khallil; Essam H. Ali; Sabreen S. Ibrahim; Elhagag Ahmed Hassan (BMC Microbiology, 2023)
Abstract In the current study, fifty-eight Ingoldain fungal species assignable to forty-one genera were recovered from two water bodies receiving the treated sewage and the effluents of oils and soaps factory at Assiut Governorate (Upper Egypt), of which Anguillospora, Amniculicola, Flagellospora, and Mycocentrospora were the most prevalent genera. The most widespread identified species were Anguillospora furtive, Amniculicola longissima and Flagellospora fusarioides. Forty-three species were identified for the first time in Egypt. The most Ingoldain taxa were estimated for El-Zinnar canal, with the highest recorded taxa in winter. Whereas, the highest dominance of Ingoldian fungi was estimated for the El-Ibrahimia canal. The highest Simpson and Shannon diversity indexes were estimated for El-Zinnar canal samples recording 0.9683 and 3.741, respectively. The poorest water sites with Ingoldian fungi were those exposed directly to either treated sewage or industrial effluents, with which relatively higher values of water conductivity, cations and anions. Water temperature was the main abiotic factor driving the seasonal occurrence of Ingoldian fungi. It is interesting to isolate some Ingoldian fungal species from the stressful water sites receiving the effluents which provide valuable insights regarding their adaptation, predictive and putative role as bioindicators and their potentiality in pollutants degradation, organic decomposition, and transformation of xenobiotic compounds.